Residents’ Attitudes, Intentions and Actual Engagement in Conservation of Built Heritage: Examining the Moderating Effect of Level of Tourism Development in Tanzania - Lwoga, Noel Biseko (Revista de turism - studii și cercetări în turism, 2016)
This study investigated factors influencing local residents' engagement in the conservation of the built heritage. It proposed a theoretical extension of the theory of planned behaviour by adding to the socio-psychological theory the tourism situational factor of "level of tourism development at the destination". A questionnaire survey was conducted with local households in Zanzibar Stone Town (N = 151) and Pangani Town (N = 88) in Tanzania. The former town is more developed in terms of tourism than the latter. The results of the structural equation modelling demonstrate that attitudes to conservation relate positively to intention to conserve, which, in turn, relates positively to (actual) engagement in conservation. The mentioned relationships are stronger among local residents in Zanzibar Stone Town that those in Pangani Town. The survey dara were triangualted by in-depth interviews with 12 local residents, which showed the importance of socio-cultural contexts in explaining the effect of tourism development. The study supports the extension of socio-psychological models with the inclusion of tourism development factor in the built heritage setting. The study discusses theoretical and managerial implications.